PENGARUH PAJAK DAERAH, DAU, DAN DAK TERHADAP BELANJA MODAL KABUPATEN/KOTA PROVINSI JAWA BARAT TAHUN 2016-2021 - Muhammad Yusuf; Ajeng Kartika Galuh (Journal of Development Economic and Social Studies, 2023)
West Java is the province in Indonesia with the highest percentage Regional Expenditure realization in 2021. However, the Capital Expenditure used is still low and tends to decrease. This study aims to determine the Effect of Local Taxes, General Allocation Funds (DAU), and Special Allocation Funds (DAK) on district/city Capital Expenditures in West Java Province in 2016-2021. This study uses a quantitative approach to analysis. The data used is secondary data originating from the Directorate General of Fiscal Balance (DJPK). The analytical method used in this research is panel data regression analysis. The results of this study showed that Local Taxes, General Allocation Funds (DAU), and Special Allocation Funds (DAK) have a significant influence on capital expenditure. Local Taxes have a negative and significant influence on Capital Expenditures, while General Allocation Funds (DAU), and Special Allocation Funds (DAK) have a positive and significant influence on Capital Expenditures. The determinant coefficient showed that the Capital Expenditure variable can be explained by the Local Tax, DAU, DAK variables of 81.74 percent, while the remaining 18.26 percent is explained by other variables outside this research model.